2008
DOI: 10.1515/bmt.2008.007
|View full text |Cite
|
Sign up to set email alerts
|

A simple measuring device for laboratory indentation tests on cartilage / Eine einfache Prüfvorrichtung für Indentationsversuche am Knorpel

Abstract: Mechanical testing of articular cartilage and repair tissue enables judgment of their capacity in withstanding mechanical loading. In the past, different methods have been developed requiring a complex technical setup and extensive data analysis. Therefore, the aim of the present project was to build up a simple measuring apparatus for laboratory indentation tests. The device consists of an incremental optical displacement transducer with a sleeve bearing guided plunger and a spherical tip made of polished ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In the past, different methods have been developed requiring a complex technical setup and extensive data analysis. 22 Therefore, a simple measuring device for laboratory indentation tests on cartilage was developed, as previously published. 24 In the present study, biomechanical properties showed significant differences among lesion tissue, remote articular cartilage, and control area specimens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the past, different methods have been developed requiring a complex technical setup and extensive data analysis. 22 Therefore, a simple measuring device for laboratory indentation tests on cartilage was developed, as previously published. 24 In the present study, biomechanical properties showed significant differences among lesion tissue, remote articular cartilage, and control area specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Data smaller than 0.02 (25-s creeping index) and more than 15 Mpa (Young’s modulus) were excluded from statistical analysis. 22 Immediately after biomechanical investigation, specimens were processed for histology by fixation in 4% buffered formalin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations